Pengaruh Pendidikan Kewirausahaan, Dukungan Keluarga, Dan Motivasi Prestasi Terhadap Minat Berwirausaha - Erwin Maulana Aditia; Pardiman Pardiman; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis research was conducted with the aim of knowing the effect of entrepreneurship education, family support and achievement motivation on the entrepreneurial interest of students of the Management Study Program, Islamic University of Malang. This study uses a population of 2018 management students who have taken entrepreneurship education courses totaling 518 students while the number of samples used in this study amounted to 83 students. The methods used in this research are validity test, reliability test, normality test, multiple linear regression analysis, classical assumption test, hypothesis test, coefficient of determination test. The results of this study indicate that entrepreneurship education has no effect on interest in entrepreneurship, family support affects interest in entrepreneurship, achievement motivation does not affect interest in entrepreneurship. Meanwhile, simultaneously shows that entrepreneurship education, family support and achievement motivation have an effect on interest in entrepreneurship. Keywords: Entrepreneurship Education, Family Support, Achievement Motivation, Entrepreneurial Interest.